Dimensi Ontologis-Etis Konsepsi Ketuhanan Islam: Analisis Hermeneutika Sintetis-Logis Fazlur Rahman dan al-Ṭabāṭabā’ī - Amrizal Amrizal (ILMU USHULUDDIN, 2019)
As as muslim, it is important to clear up the view of the Godness in Islam which is often misunderstood by some people. Its urgency not only as an enlightment for nonmuslim on Islam, moreover to some of muslim community today. One of those is the accusation which the conception of God in Islam is arbitrarily, cruel, desire to worshipped, requires to defensed brutally, etc. Fazlur Rahman has tried to answer this accusation using Synthetic-Logical Hermenenutics by describing three important conceptions about God in al-Qur’an, namely: the dependency of everything to God, the mercy of God, and the necessary relation between God and human. However, Fazlur Rahman elaborated Moral-Ethical aspect only, minus ontological aspect which is precisely important to answer the accusation above. This minus can be very well covered by `Allamah al-Ṭabāṭabā’ī’s Tafsīr. By the synthesis of both, the accusation is not only indisputable, but will provide a profound explanation on Godness in Islam. So, then it will appear that the conception of God in Islam not only has a dimension of theological-ethic but firmly philosophical-theoritic.